Impact of subtrochanteric fractures in the geriatric population: better pre-fracture condition but poorer outcome than pertrochanteric fractures: evidence from the Spanish Hip Fracture Registry - Héctor J. Aguado; Pablo Castillón-Bernal; Paula S. Ventura-Wichner; María C. Cervera-Díaz; Javier Abarca-Vegas; Luis García-Flórez; Jordi Salvador-Carreño; Virginia García-Virto; Clarisa Simón-Pérez; Cristina Ojeda-Thies; Pilar Sáez-López; Juan I. González-Montalvo; et al. (Journal of Orthopaedics and Traumatology, 2022)
Abstract Background Clinical management in orthogeriatric units and outcome indicators are similar for extracapsular fragility hip fractures, without discriminating between subtrochanteric and pertrochanteric fractures. Hypothesis Geriatric patients, 75 years or older, with subtrochanteric fractures have worse clinical and functional outcomes than those with pertrochanteric fractures. Materials and methods Retrospective observational study of data prospectively collected by the Spanish Hip Fracture Registry including patients 75 years or older, admitted for extracapsular hip fractures from January 2017 to June 2019. Demographic and baseline status, pre-operative, post-operative and 30-day follow-up data were included. Results A total of 13,939 patients with extracapsular hip fractures were registered: 12,199 (87.5%) pertrochanteric and 1740 (12.5%) subtrochanteric. At admission, patients with subtrochanteric fractures were younger (86.5 ± 5.8 versus 87.1 ± 5.6 years old), had better pre-fracture mobility (3.7 ± 2.7 versus 3.9 ± 2.8) (1-to-10 scale, 1 being independent) and were more likely to be living at home; those with pertrochanteric fractures had worse cognitive function (Pfeiffer 3.3 ± 3.3 versus 3.8 ± 3.5). The subtrochanteric fracture group showed worse post-fracture mobility (7.3 ± 2.7 versus 6.7 ± 2.7) and greater deterioration of mobility (3.7 ± 3.0 versus 2.9 ± 2.7). Among individuals living at home at baseline, those with subtrochanteric fractures were more likely to remain in an assisted facility at 30-day follow-up. In-hospital mortality during acute admission was higher for the subtrochanteric group (5.6% versus 4.5%) (p = 0.028). To our knowledge, this is the first paper highlighting the differences between these two fracture groups in the geriatric population. Conclusions Subtrochanteric fractures in the older population are a different and worse entity, with greater morbimortality and functional decline than pertrochanteric fractures. Despite being younger and fitter at admission, older patients with subtrochanteric fractures have a higher risk of remaining non-weight bearing and undergoing re-operation and institutionalization. Orthogeriatric units should be aware of this and manage subtrochanteric fractures accordingly. Level of evidence: IV.